ROLE OF DEMOGRAPHIC FACTORS IN SHAPING GREEN PRODUCT AWARENESS IN KAMRUP METRO DISTRICT OF ASSAM - Dahal, Debajit; Singh, Amrit Pal (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The global environmental crisis has heightened the importance of green products yet their adoption in developing regions like India remains limited due to low consumer awareness. This study investigates the influence of demographic factors (age, gender, income, and education) on green product awareness among consumers in Kamrup Metro district of Assam, a region with a nascent green market. Using a quantitative and cross-sectional research design, data were collected from 150 adult respondents via a structured questionnaire. Statistical analyses including Mann-Whitney U and Kruskal-Wallis tests, reveal that income and education significantly shape green product awareness, with higher-income and more educated consumers exhibiting greater awareness due to better access to information and resources. In contrast, age and gender show no significant impact, suggesting uniform exposure to environmental information across these groups. These findings highlight the need for targeted awareness campaigns focusing on educated and affluent consumers while addressing economic barriers for lower-income groups. The study contributes to the literature on green consumerism in developing regions and offers practical insights for businesses, policymakers, and environmental advocates to promote sustainable consumption in Assam.